ENVIRONMENTAL, SOCIAL AND GOVERNANCE PERFORMANCE ON THE ROMANIAN CAPITAL MARKET - VASIU Diana Elena (Management of Sustainable Development, 2023)
The approach of sustainability from an ESG perspective is used worldwide for over 50 years, but on the Romanian Capital Market, is still extremely modest, only a small number of listed companies reporting on their ESG performance. However, this scenario is anticipated to change starting with financial year 2023, as new regulations from the European Union will mandate non-financial Environmental, Social, and Governance (ESG) performance reports. This development will generate new challenges for professionals in the field, while also presenting new opportunities for ranking companies based on sustainability performance. Using ESG scores from Refinitiv, the purpose of this article is to present the ranking of listed Romanian companies from the ESG perspective, at the level of the 2022 and 2021 fiscal years. Results show that a very limited number of companies listed on the Romanian capital market can be evaluated from Refinitiv ESG scores perspective, but in general, the evaluated companies often record satisfactory values of these scores